2012
DOI: 10.1038/ki.2011.477
|View full text |Cite
|
Sign up to set email alerts
|

IgA antibodies against β2 glycoprotein I in hemodialysis patients are an independent risk factor for mortality

Abstract: Cardiovascular complications are the most important cause of death in patients on dialysis with end-stage renal disease. Antibodies reacting with β-glycoprotein I seem to play a pathogenic role in antiphospholipid syndrome and stroke and are involved in the origin of atherosclerosis. Here we evaluated the presence of anticardiolipin and anti-β-glycoprotein I antibodies together with other vascular risk factors and their relationship with mortality and cardiovascular morbidity in a cohort of 124 hemodialysis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…[21][22][23] Our group has recently described an increased prevalence of IgA aB2GPI in patients on hemodialysis (33%) and their association with thrombotic events and mortality. 24 This finding was subsequently confirmed by another study. 25 However, the influence of these autoantibodies after renal transplantation is unknown, particularly in the first postoperative period when thrombotic events are more frequent.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…[21][22][23] Our group has recently described an increased prevalence of IgA aB2GPI in patients on hemodialysis (33%) and their association with thrombotic events and mortality. 24 This finding was subsequently confirmed by another study. 25 However, the influence of these autoantibodies after renal transplantation is unknown, particularly in the first postoperative period when thrombotic events are more frequent.…”
supporting
confidence: 78%
“…44 The prevalence of pretransplant IgA aB2GPI antibodies is found in one third of transplanted patients, which is a number similar to that previously reported in patients on hemodialysis. 24,25 This finding raises the question of why only a few patients positive for IgA aB2GPI antibodies developed this thrombotic complication in the first weeks after renal transplantation. This situation is well known in patients with aPL, in whom the presence of antibodies is not sufficient to induce thrombosis formation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Serrano et al [124] reported that they were the most common isotype of anti-β2GPI in hemodialysis patients. In a large multi-center, multi-ethnic cohort (LUMINA), Murthy et al reported that isolated IgA anti-β2GPI was associated with thrombosis [125].…”
Section: Iga Autoantibodies and Smokingmentioning
confidence: 98%
“…80 In a large retrospective study of 160 patients with primary APS, only one developed end-stage renal disease.24 Similarly, only one patient with end-stage renal disease was noted in a prospective study of 39 patients with primary APS.78 IgA antibodies against B2GPI in patients receiving haemodialysis have been suggested as an independent risk factor for mortality. 81 The pathogenic role of the IgA isotype, however, remains unclear and studies are needed to investigate the clinical relevance of these antibodies.82 Several studies investigating the clinical relevance of aPL in patients who underwent renal transplantation increased the risk of graft failure and thrombosis at any site within the renal vasculature. [83][84][85] McIntyre and Wagenknecht86 reported that among 110 transplant recipients, those with aPL at the time of transplantation had a higher rate of early renal allograft failure than those without aPL.…”
Section: Arterial Hypertensionmentioning
confidence: 99%